Pengaruh Gross Domestic Product (GDP),Earning Per Share (EPS), Return on Asset (ROA),Market Value Added, dan Debt to Equity Ratio (DER) (Studi Empiris Pada Perusahaan Indeks LQ45 Di BEI Periode 2018-2020) - Hanik Latifah; Ronny Malavia Mardani; Etty Saraswati (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis study aims to determine how the influence of gross domestic product (GDP), earnings per share (EPS), Return on Assets (ROA), market value added (MVA), and debt to equity ratio (DER) to stock prices empirical studies in companies that listed on the LQ45 index on the Indonesian stock exchange in 2018-2020. The population in this study are all companies included in the LQ45 index listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period with 57 companies. Sampling technique using purposive sampling method obtained data samples of 27 companies. This research data collection method uses the method of data documentation listed in the annual report (IDX). The data analysis technique in this study used panel data regression with software eviews 9. The results showed that partially gross domestic product (GDP) and earnings per share (EPS) had a positive and insignificant effect on stock prices. Return on Assets (ROA) and Market Value Added (MVA) had a positive and significant effect on stock prices, and the Debt to Equity Ratio (DER) has a negative and significant effect on stock prices. Keywords: Gross Domestic Product (GDP), Earning Per Share (EPS), Return on Assets (ROA), Market Value Added, Debt to Equity Ratio (DER), Stock